Rising Kidnapping Incidents in the Federal Capital Territory, Abuja: An Overview of Its Threat to Safety of Lives and Property - Nwosu, Chimezie; Okpoebo, Casmir Chukwudi; Ilori, Gabriel Oluwaseun; Ilori, Mercy Olanike (Kashere Journal of Politics and International Relations, 2023)
The focus of this paper is to bring to the fore the reality of and rising cases of kidnappings as an existential threat to safety of lives and property in the Federal Capital territory, Abuja. The study postulates the Kidnappings and abductions have emerged in the FCT as it is in several other parts of the country. Criminality and ritual killings, political ambitions, lack of requisite consequences for offenders, general insecurity, and involvement of security agencies, unemployment and poverty were identified as some of the causes. Loss of money in the payment of ransom, emotional and trauma for both victims and their loved ones, decline in the number of potential investors, forced/early marriage of victims and above all, deaths were identified as consequences of kidnappings. Data for the study were obtained from secondary sources including text books, academic journals and credible online sources while the rational choice and the broken window theories were adopted. The study concludes that the Federal government and the FCT administration must synergize in providing an enabling environment for job creation, there must be transparency and decisiveness in dealing with suspected kidnappers in order to help restore public support and confidence in the people and visitors alike, to address kidnappings in the FCT, insecurity in neighboring states such as Nasarawa, Kaduna and Niger must be confronted frontally, intentionally and sincerely, activities of security personnel should be brought under strict scrutiny to fish out bad eggs and promote security and peace education in school.